2006
DOI: 10.1007/s00405-006-0050-x
|View full text |Cite
|
Sign up to set email alerts
|

Huge retropharyngeal lipoma causing obstructive sleep apnea: a case report

Abstract: Lipoma of the retropharyngeal space is a very rare benign tumor often causing unspecific clinical symptoms. The most common symptoms are dysphagia and/or respiratory disturbances. The clinical diagnosis may be difficult. The radiological imaging techniques (CT and MRI) can provide adequate information with regard to the composition and extension of the tumor, although final histological confirmation is essential. Surgery is the treatment of choice. We present a case of 40-year-old male patient complaining of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 5 publications
0
23
0
3
Order By: Relevance
“…Although there are many surgical approaches in treatment of retropharyngeal lipomas, the best surgical field of view can be obtained by a transcervical approach, which is preferred for huge retropharyngeal lipomas. [6] As in our case, this approach enables a larger field of view and total excision of the mass.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Although there are many surgical approaches in treatment of retropharyngeal lipomas, the best surgical field of view can be obtained by a transcervical approach, which is preferred for huge retropharyngeal lipomas. [6] As in our case, this approach enables a larger field of view and total excision of the mass.…”
Section: Discussionmentioning
confidence: 59%
“…The most common symptoms are wheezing, dyspnea, dysphagia and snoring as in our case. [4,6,7] The mass should reach quite huge dimensions to cause OSA as previously reported in a few cases. [1,6] In our case, the OSA symptoms which were present for a long time were investigated with preoperative PSG and severe OSA (AHI: 75) was determined.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Retropharyngeal lipoma case is not clearly described in the literature study, as shown in Table 1 that since 1877 until now, not more than 46 cases are reported, including this case. symptoms, depending on the affected part of aero digestive tract, such as nasal obstruction, tightness, hoarseness, snoring, and a sense of prop when swallowing food, depend on the location and size of the tumor [3,6,[10][11][12][13]. The patient had early symptoms of nasal obstruction during sleeping on right side and prop sense when swallowing, followed by longer process of swallowing, snoring, hoarseness, and dyspnea while sleeping.…”
Section: Discussionmentioning
confidence: 99%
“…Overnight polysomnography (PSG) was used to determine the apneaehypopnea index (AHI Factors that increase the vulnerability of OSA include age, gender, obesity, family history, menopause, craniofacial abnormalities, and certain health behaviors such as cigarette smoking and alcohol abuse. 1,3 Although craniofacial abnormalities have an effect on patients with OSA, these significantly vary among patients with (1) enlarged soft tissues such as the tongue base and palate, 4,5 (2) narrowing of the pharyngeal space due to anatomic abnormalities, 6,7 and (3) loss of function of the pharyngeal space due to anatomic abnormalities. 8 Thus, patients who were successfully treated for head and neck cancers often have a partially obstructed upper airway, which is functional during the day but collapses during sleep.…”
mentioning
confidence: 99%